A Large Paleoearthquake in the Central Apennines, Italy, Recorded by the Collapse of a Cave Speleothem. Issue 10 (28th September 2020) - Pace, Bruno; Valentini, Alessandro; Ferranti, Luigi; Vasta, Marcello; Vassallo, Maurizio; Montagna, Paolo; Colella, Abner; Pons‐Branchu, Edwige
Abstract: Speleoseismological research carried out in the Central Apennines (Italy) contributed to understanding the behavior of active normal faults that are potentially able to generate Mw 6.5–7 earthquakes documented by paleoseismology and by historical and instrumental seismology. Radiometric (U‐Th, AMS‐ 14 C, and bulk‐ 14 C) dating of predeformation and postdeformation layers from collapsed speleothems found in Cola Cave indicates that at least three speleoseismic events occurred in the cave during the last 12.5 ka and were ostensibly caused by seismic slip on one or more of the active faults located in the region surrounding the cave. We modeled the collapse of a tall (173 cm high) stalagmite to find a causative association of this event with one among the potential seismogenic sources. We defined the uniform hazard spectrum (UHS) for each seismogenic source at the site, and we used the calculated spectra in a deterministic approach to study the behavior of the speleothem, through a numerical finite element modeling (FEM). Although our analysis suggests the "Liri" fault as the most likely source responsible for the ground shaking recorded in the cave, the "Fucino" fault system, responsible for a Mw 7 earthquake in 1915, cannot be excluded as a potential source of speleoseismic damage. Results of this work provide new constraints on the seismotectonic history of this sector of Central Apennines and highlight the performance of integrated speleoseismological, seismic hazard, and numerical studies. Key Point: Performance of integrated speleoseismological, seismic hazard and numerical studies